2019
DOI: 10.1097/mjt.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Which Combination Treatment Is Better for Spinal Metastasis: Percutaneous Vertebroplasty With Radiofrequency Ablation, 125I Seed, Zoledronic Acid, or Radiotherapy?

Abstract: PVP combined with I seed exhibited the best clinical efficacy in terms of VAS, PVP combined with RT was the best choice in terms of WHO Pain Relief, and PVP combined with RFA showed the best effect in terms of ODI for the treatment of SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
17
0
8
Order By: Relevance
“…Many factors such as the type of fracture, surgical technique, surgeon's experiences, suitable implanting location, and proper dose of 125 I particles are usually the key to increase the therapeutic efficacy of this combined surgery and reduce risks, especially the suitable implantation location and fitted dose of 125 I particles that may bring better therapeutic effectiveness and can avoid radioactive myelopathy, which have been emphasized in previous published literatures [6, 10, 12, 14, 15]. Thus, the surgeon should have skilled technique and rich experience of PVP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors such as the type of fracture, surgical technique, surgeon's experiences, suitable implanting location, and proper dose of 125 I particles are usually the key to increase the therapeutic efficacy of this combined surgery and reduce risks, especially the suitable implantation location and fitted dose of 125 I particles that may bring better therapeutic effectiveness and can avoid radioactive myelopathy, which have been emphasized in previous published literatures [6, 10, 12, 14, 15]. Thus, the surgeon should have skilled technique and rich experience of PVP.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing five related published clinical studies [6, 10, 12, 14, 15], the following seven main items of indications for PVP plus implantation of 125 I particles had been summarized (Figure 6). Firstly, the definite radiographic and physical evidences to confirm spinal metastasis were emphasized in five clinical studies [6, 10, 12, 14, 15]. Secondly, three literatures revealed that back pain with or without neck pain should be considered as the major clinical symptom [10, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of spine metastases, combining percutaneous vertebroplasty (decreasing pain through restoring mechanical stability of vertebrae) with radiation therapy (exhibiting antitumor effect) provides better pain relief than radiotherapy alone [49] (Figure 3).…”
Section: Painful Bone Metastasesmentioning
confidence: 99%
“…Several doses per fraction are used, from single 15–24 Gy fractions to 18–36 Gy delivered in 1–5 fractions [57,58,59,60,61,62]. Of note, data concerning efficacy and safety of the treatment come from retrospective analyses [46,47,48,49,50,51]. Nevertheless, SRS/SBRT is widely used in most radiation therapy centres.…”
Section: Painful Bone Metastasesmentioning
confidence: 99%